CONCEPT MAPPING – AN EFFECTIVE TOOL TO PROMOTE CRITICAL THINKING SKILLS AMONG NURSES - Nirmala, T.; Shakuntala, B. S. (Journal of Health and Allied Sciences NU, 2011)
Title: Effect of Concept Mapping in Development of Critical thinking (CT) Skills among B. Sc Nursing StudentsObjectives: To evaluate the effectiveness of concept mapping as a teaching strategy to develop critical thinking skills.Materials and Methods: Pretest, post test control group design was used. The IV year B.Sc nursing students were included as experimental group (n=40) and control group (n=44). The experimental group was given a training to prepare nursing care plans using concept mapping. The training programme was for 12 weeks where the participants were given case study scenarios every week to prepare nursing care plans using concept map. The experimental group and control group were again assessed for the critical thinking skills. The concept maps were evaluated using scoring criteria.Results: In the post test, there was a significant difference in the critical thinking scores of both the groups at 0.05 level. (t=2.16). A significant improvement was identified between the pretest and post test critical thinking scores of experiment group at 0.05 level (t=2.0). Comparison of concept mapping scores of the experimental group in the pretest and post test showed a highly significant difference at 0.041 level.Conclusion: The study was able to show a significant improvement in the critical thinking skills of nursing students. However, the critical thinking scores were poor due to the high standard of the assessment tool. It is needed to develop critical thinking skill assessment tool which will suit the nursing community and further research is required to promote concept mapping as a teaching and learning strategy.
Keywords: Concept Mapping; Critical thinking; nursing process